ANALISA KINERJA JARINGAN WIMAX & UNTUK APLIKASI VIDEO STREAMING (STUDI KASUS DI LAB TEKNIK ELEKTRO FAKULTAS TEKNIK UNIVERSITAS RIAU) - Yaldi, Jefri; Febrizal, Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
WiMax (World wide Interoperability for Microwave Access) is a standard Broadband Wireless Access with the ability to provide high speed data services to a wider area which is powered by a standard IEEE 802.16d (802.16-2004). Wimax technology supports multiple services one of which is video streaming. The purpose of this study was to analyze the performance of network devices wimax in the Lab Electrical Engineering Faculty of Engineering, University of Riau to access the streaming video service. This study did some test scenarios include using two clients (point-tomultipoint) and one client (point-to-point), add a distance of 5 meters, 10 meters to 15 meters, 20 meters and additional traffic load (video resolution) 360p , 480p, 720p and 1080p. The method used is the method of packet sniffing for 300 seconds using software wireshark to see Quality of servive (QoS). QoS parameters analyzed such as throughput, delay, packet loss and jitter. Analysis of best measurement was obtained at a distance of 5 meters with 360p video resolution by throughput 7638.54975 Byte / s, delay 0.15136306 s, packet loss 0% and jitter 0.30060517 s by using two client. And at a distance of 20 meters with 1080p video resolution by throughput 8053.490398 Byte / s, delay 0.082082906 s, packet loss 0% and jitter 0.156352979 s by using one client. . Keyword: Wimax, Video streaming, QoS, Packet sniffing